Application of transglutaminase in meat systems with different protein sources - Yepishkin, Serhii; Strashynskyi, Igor; Pasichnyi, Vasyl; Safonik, Nazarii (My University, 2023)
One of the important directions by which to ensure public health is to expand the range of products for a healthy diet, which are characterized by high nutritional and biological value and include essential components in balanced ratios. A balanced diet provides full vitality and helps to prevent pathological disorders and human diseases. It is important to study approaches that use the application of plant raw materials with proven functional properties in the technology of combined products, which allows one to modify the composition and adjust the technological properties of food accordingly. Одним із важливих напрямів забезпечення здоров’я населення є розширення асортименту продуктів здорового харчування, які характеризуються високою харчовою та біологічною цінністю та містять незамінні компоненти у збалансованих співвідношеннях. Збалансоване харчування забезпечує повноцінну життєдіяльність і допомагає запобігти патологічним розладам і захворюванням людини. Актуальним є вивчення підходів із застосуванням у технології комбінованих продуктів рослинної сировини з доведеними функціональними властивостями, що дозволяє модифікувати склад та відповідним чином коригувати технологічні властивості харчових продуктів.
Keywords: кафедра технології м’яса і м’ясних продуктів; м’ясні продукти; transglutaminase; vegetable raw materials; meat products; трансглутаміназа; рослинна сировина